Aktivitas Antibakteri Membran Nanokomposit Kitosan/Nanopartikel Perak - Notriawan, Doni; Nesbah, Nesbah; Ernis, Gustria; Fadhila, Muhammad Adeng; Wibowo, Risky Hadi; Pertiwi, Reza; Ilfanisari, Vinolla (ALCHEMY, 2021)
The aim of this study was to make and test the antibacterial activity of chitosan/silver nanoparticles nanocomposite membranes. Nanocomposite membranes were synthesized by chitosan with pluronic using acetic acid as a solvent. Silver nanoparticles were synthesized using the green synthesis method and the makasar fruit (Brucea javanica L. Merr) peel extract as a bioreductor. The silver nanoparticles were composited with a chitosan/pluronic mixture and printed on a glass plate. Nanocomposite membranes were characterized using the FTIR spectrophotometer and the scanning electron microscope (SEM). Nanocomposite membrane were tested for antibacterial activity against Escherechia coli. The UV-Vis spectra showed the formation of silver nanoparticles which were indicated by the absorption at 454 nm and the absorbance value of 0.405. Characterization using FTIR showed no new functional groups formed in the composites of chitosan and pluronic. SEM results showed the difference between the chitosan membrane and the nanocomposite membrane. The surface of nanocomposite membrane showed uneven compared to the chitosan membrane. Nanocomposite membranes have antibacterial activity to inhibit E. coli growth.   Keywords: nanocomposite, chitosan/silver nanoparticles, antibacterial Penelitian ini bertujuan untuk membuat dan menguji aktivitas antibakteri membran nanokomposit kitosan/nanopartikel perak. Membran nanokomposit dibuat dengan mensintesis kitosan dengan pluronik menggunakan pelarut asam asetat. Nanopartikel perak disintesis menggunakan metode green synthesis dengan ekstrak kulit buah makasar (Brucea javanica L. Merr) sebagai bioreduktor. Nanopartikel perak dikompositkan dengan campuran kitosan/pluronik dan dicetak di atas plat kaca. Membran nanokomposit dikarakterisasi menggunakan spektrofotometer FTIR dan scanning electron microscope (SEM). Membran nanokomposit dilakukan uji aktivitas antibakteri terhadap Escherechia coli. Spektra UV-Vis menunjukkan terbentuknya nanopartikel perak yang ditandai adanya serapan pada panjang gelombang 454 nm dan absorbansi 0,405. Karakterisasi dengan FTIR menunjukkan tidak adanya gugus fungsi baru yang terbentuk pada komposit dari kitosan dan pluronik. Hasil SEM menunjukkan adanya perbedaan antara membran kitosan dengan membran nanokomposit. Permukaan membran nanokomposit terlihat tidak rata dibandingkan membran kitosan. Membran nanokomposit memiliki aktivitas bakteri sehingga dapat mengambat pertumbuhan bakteri E. coli. Kata kunci: nanokomposit, kitosan/nanopartikel perak, antibakteri